Comparison of the results of bipolar transurethral enucleation and resection of the prostate with and without morcellation in treatment of benign prostatic hyperplasia - Weerasawin, Thatree (Insight Urology, 2023)
Objective: To compare the result of bipolar transurethral enucleation and resection of the prostate with morcellation (B-TUERP-M) and without morcellation (B-TUERP) in treatment of benign prostatic hyperplasia. Materials and Methods: This was a prospective single centre cohort study of 101 patients with prostate enlargement of more than 60 ml who underwent B-TUERP by a single surgeon between January 2020 and June 2022. Patients were divided into two groups, a B-TUERP group of 49 patients and a second group of 52 patients classed as B-TUERP-M. The perioperative outcomes followed up at 1, 3 and 6 months after surgery were evaluated. Results: There were no significant differences in the preoperative parameters of the two groups. Comparisons between the two groups showed a shorter operative time (63.94 ± 12.01 vs 77.77 ± 11.80 min, p-value 0.000), more resected prostate tissue (65.73 ± 14.67 vs 60.73 ± 5.45 gm, p-value 0.027) and a higher post-operative hematocrit level (35.16 ± 3.97 vs 33.18 ± 3.22%, p-value 0.007) in the patients who underwent B-TUERP with morcellation. At 6 months after the procedure, better results were found in patients who had undergone B-TUERP-M regarding urine flow rate (26.33 ± 5.33 vs 20.66 ± 5.08 ml/sec, p-value 0.000), post-void residual urine volume (24.19 ± 10.93 vs 36.04 ± 16.90 ml, p-value 0.000), post-operative PSA (0.72 ± 0.43 vs 1.22 ± 0.54 mg/ml, p-value 0.000) and International Prostate Symptom Scores (5.01 ± 1.36 vs 5.71 ± 1.33, p-value 0.001). Conclusion: Better outcomes occurred following B-TUERP with morcellation with regard to operative time, resection weight of prostatic adenoma, post-operative urine flow rate, Post-void residual urine volume, PSA and International Prostate Symptom Score than in patients treated with B-TUERP without morcellation.